2013
DOI: 10.4028/www.scientific.net/amr.690-693.602
|View full text |Cite
|
Sign up to set email alerts
|

Structural Stability, Electronic and Optical Properties of Ni-Doped Boron Carbide by First Principles Calculation

Abstract: The wide band gap, temperature stability, high resistivity, robustness of semiconducting boron carbide make it an attractive material for device applications.. Here the structural stability along with the electronic and the optical properties of Ni-doped boron carbides (B13C2) were studied using the first principle calculations based on plane wave pseudo-potential theory. The calculated results showed that Ni-doped in boron carbide was in preference to substituting C atom on the end of C-B-C chain, but it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…doped B 13 C 2 ( Figure ) with Fe and calculated a band gap of 0.51 eV, suggesting that the extended states of 3d band of Fe could increase the electrical conductivity. [ 155,159 ] Fan et al. reported by DFT calculations that when Ni preferentially substitutes the C atoms in BC at the end of the C‐B‐C chain instead of the B atoms.…”
Section: Families Of Known Boridesmentioning
confidence: 99%
See 1 more Smart Citation
“…doped B 13 C 2 ( Figure ) with Fe and calculated a band gap of 0.51 eV, suggesting that the extended states of 3d band of Fe could increase the electrical conductivity. [ 155,159 ] Fan et al. reported by DFT calculations that when Ni preferentially substitutes the C atoms in BC at the end of the C‐B‐C chain instead of the B atoms.…”
Section: Families Of Known Boridesmentioning
confidence: 99%
“…[158] Feng et al reported that B 4 C-Si-B composites consolidated by SPS exhibit lower 𝜅 but reach a low zT value of 0.036 at 1000 K for the sample with 10 wt% Si and 5.6 wt% B. Qin et al doped B 13 C 2 (Figure 8) with Fe and calculated a band gap of 0.51 eV, suggesting that the extended states of 3d band of Fe could increase the electrical conductivity. [155,159] Fan et al reported by DFT calculations that when Ni preferentially substitutes the C atoms in BC at the end of the C-B-C chain instead of the B atoms. The weaker Ni-B covalent bond decreases 𝜅.…”
Section: Boron Carbidesmentioning
confidence: 99%